Elaboração e validação de escala diagramatica para ferrugem da candeia e progresso da doença no campo - Pereira, Renata Cristina Martins (2017)
Candeia (Eremanthus erythropappus (DC.) MacLeish), a native forest species from South America, has raised commercial interest due to its high resistance raw timber, durability and the production of an essential oil that contains the alphabisabolol, widely used in the pharmaceutical industry of cosmetics. However, plant diseases can severely reduce productivity and compromise their supply in the Brazilian market. The rust in candeia is caused by the pathogen Puccinia velata which occurs in the field plantations in adult trees. However, there is no data or basic research to determine control and management strategies. Therefore, the objective of this work was to create a standardized method to quantify the severity of rust in field plantations and observe temporal progression of the disease during a year. Before the first objective, a diagrammatic scale was developed with eight values: 0,25, 0,50, 1, 2, 4, 8, 16, 32% of disease severity, based on the frequency ranges found in the field plantations. From the leaves collected in the field, 95% of them presented severity below 16% and only 5% had it between 16 and 32%. The use of the scale provided the evaluators with good levels of accuracy, precision, repeatability and reproducibility. Thus, the scale proved to be adequate for the quantification of rust in “candeia”. Subsequently, to this visual method of quantification, the disease progress was also evaluated for 17 clones of E. erythropappus in an experimental field at the Federal University of Lavras. The monitoring of the disease was done monthly from September 2016 to July 2017. Three empirical models were then adjusted to describe the disease, a mean test for the AACDP values was performed to evaluate resistance of the clones and the correlation between the conditions and the progress of rust. In spite of presenting symptoms of the pathogen during the whole evaluated period, epidemic outbreaks occurred in the month of March, having an highest incidence of the disease, affecting about up to 90% of the trees in the field plantations. The best model adjusted for the seven clones evaluated in the epidemic disease period was Exponential. Scott-Knott test separated the clones into three clusters: the first with eight moderately resistant clones, the second with six moderately susceptible clones and the third with three susceptible clones. The correlation of the climatic variables with the severity in the field indicated that only temperature influences the progress of the disease.